HUBUNGAN KEHAMILAN GANDA DAN KELAINAN LETAK JANIN DENGAN KEJADIAN KETUBAN PECAH DINI DI RUMAH SAKIT UMUM DAERAH KOTA PRABUMULIH TAHUN 2019 - Dwi Saputri Mayang Sari (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2020)
Early rupture of membranes (KPD) is defined as premature rupture of membranes. This can occur late in pregnancy or long before the time of delivery. Premature rupture of membranes is a complication associated with gestational pregnancy and has a major contribution to the perinatal mortality rate in infants who are preterm. The purpose of this study was to determine the relationship between multiple pregnancy and fetal abnormalities with the occurrence of premature rupture of membranes in the Prehumulih City General Hospital in 2019.This study uses an Analytical Survey using a Cross Sectional approach. The population of this study was mothers who gave birth in the pre-Sumatran city general hospital in 2019 totaling 1712 people. The number of samples in this study were 324 respondents. In the univariate analysis, it is known that of 324 respondents found that mothers who were diagnosed with multiple pregnancy were 163 respondents (50.3%) while mothers who were not diagnosed with multiple pregnancy were 161 respondents (49.7%) and mothers who were diagnosed with fetal abnormalities were 163 respondents ( 50.3%) while mothers who were not diagnosed with fetal abnormalities were 161 respondents (49.7%). Bivariate analysis shows multiple pregnancy has a significant relationship with the incidence of premature rupture of membranes (p value 0,000) and fetal abnormalities have a significant relationship with the incidence of premature rupture of membranes (p value 0,000). The conclusion of this study is that there is a relationship between multiple pregnancy and abnormalities in fetal location and the incidence of premature rupture of membranes in the Prehumulih City General Hospital in 2019. Ketuban Pecah Dini (KPD) didefinisikan sebagai pecahnya ketuban sebelum waktunya melahirkan. Hal ini dapat terjadi pada akhir kehamilan maupun jauh sebelum waktunya melahirkan. Ketuban pecah dini merupakan komplikasi yang berhubungan dengan kehamilan kurang bulan dan mempunyai kontribusi yang besar pada angka kematian perinatal pada bayi yang kurang bulan. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kehamilan ganda dan kelainan letak janin dengan kejadian ketuban pecah dini di rumah sakit umum daerah kota prabumulih tahun 2019. Penelitian ini menggunakan Survey Analitik dengan menggunakan pendekatan Cross Sectional. Populasi penelitian ini adalah ibu yang melahirkan di rumah sakit umum daerah kota prabumulih tahun 2019 berjumlah 1712 orang. Jumlah sampel pada penelitian ini adalah 324 responden. Pada analisa univariat diketahui bahwa dari 324 responden didapatkan ibu yang didagnosa kehamilan ganda sebanyak 163 responden (50,3%) sedangkan ibu yang tidak didiagnosa kehamilan ganda sebanyak 161 responden (49,7%) dan ibu yang didagnosa kelainan letak janin sebanyak 163 responden (50,3%) sedangkan ibu yang tidak didiagnosa kelainan letak janin sebanyak 161 responden (49,7%). Analisa Bivariat menunjukkan kehamilan ganda mempunyai hubungan yang bermakna dengan kejadian ketuban pecah dini (p value 0,000) dan kelainan letak janin mempunyai hubungan yang bermakna dengan kejadian ketuban pecah dini (p value 0,000). Simpulan dari penelitian ini adalah bahwa ada hubungan antara kehamilan ganda dan kelainan letak janin dengan kejadian ketuban pecah dini di rumah sakit umum daerah kota prabumulih tahun 2019.